An expert in absentia: a case study for using technology to support recording studio practice. Issue 2 (1st December 2009) - King, Andrew
This article examines the use of a Learning Technology Interface (LTI) to support the completion of a recording workbook with audio examples over a ten-week period. The Virtual Learning Environment (VLE) provided contingent support to studio users for technical problems encountered in the completion of four recording tasks.Previous research has investigated how students collaborate and problem-solve during a short session in the recording studio using technology as a contingent support tool. In addition, online message boards have been used to record problems encountered when completing a prescribed task (critical-incident recording).A mixed-methods case study approach was used in this study. The students' interactions within the LTI were logged (i.e. frequency, time, duration and type of support) and their feedback was elicited via a user questionnaire at the end of the project. Data for this study demonstrate that learning technology can be a successful support tool, and also highlight the frequency and themes concerning the types of recording-practice information accessed by the learners.